The Influence of Return on Assets and Earnings Per Share on Stock Prices in IDX High Dividend 20 Companies for the 2022-2024 Period - Suri, Dhiya Septi Wulan; Aulia, Azwani; Taufik, Haviz (Multidisciplinary Journal of Education , Economic and Culture, 2026)
This study examines how Return on Assets (ROA) and Earnings Per Share (EPS) influence stock prices, focusing specifically on companies included in the IDX High Dividend 20 index during the 2022–2024 period. The analysis uses secondary data obtained from financial statements and stock price records, which are processed using panel data regression. Model selection was carried out through the Chow, Hausman, and Lagrange Multiplier tests, resulting in the Common Effect Model (CEM) as the most appropriate approach. To enhance the robustness of the estimates, White period standard errors were applied. The results reveal an interesting pattern: ROA shows a negative and significant relationship with stock prices, while EPS has a positive and significant effect. When examined simultaneously, both variables contribute meaningfully to explaining stock price variation. These findings suggest that, within high-dividend companies, investors tend to place greater emphasis on earnings per share rather than asset-based profitability when making investment decisions